What Lies Beneath English Major Students' Attitudes towards ChatGPT for Academic Writing: A TAM Perspective? - Herwanto, Wanda Hijriani; Setiawan, Slamet; Munir, Ahmad (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the perceived usefulness and ease of use of ChatGPT among English majors. The study used a qualitative case study research design to gain an idea of the experiences and perceptions of major English students at a university in East Java, Indonesia. Participants in this study are six undergraduates from the major in English at an Indonesian university. Data collection is conducted using open-ended questionnaires and interviews with selected undergraduates. The Technology Acceptance Model (TAM) framework is used as an analysis lens to identify trends and interpretations of students' attitudes of ChatGPT for academic writing. The results of this study indicate that students majoring in English have mixed attitudes to ChatGPT, some students find it useful and others prefer alternative tools for their academic writing assignments. Finally, this study emphasizes the importance of understanding individual preferences and needs when considering the integration of AI tools into academic environments.